Redesain Kursi Kuliah Ergonomis Menggunakan Pendekatan Antropometri Pada Program Studi Teknik Industri Universitas Islam Syekh Yusuf Tangerang - Hadiyansyah, Febi; Juhara, Sutresna; Rahayu, Monita (UNISTEK, 2021)
The chair is one of the tools to support lecture activities at Industrial Engineering UNIS Tangerang. Based on the Nordic Body Map that has been distributed to UNIS Industrial Engineering students, there are several complaints felt by students when using the lecture chair that is currently used. The complaint is in the form of aches or pains in the limbs, including in the neck, back, waist, legs, right hand and buttocks. This indicates that the design of the lecture chair currently used is not in accordance with the anthropometry of the UNIS Industrial Engineering students. This research method uses an anthropometric approach by taking anthropometric data from students and then identifying the lecture chairs used at this time. The next stage is about processing anthropometric data, entering the wishes of students based on the level of interest in designing the design. The results showed that the redesign of the lecture chair with a new minimalist design and has the advantage that the back of the chair and the seat mat have used foam material so that it is more comfortable, there is a shelf for storing goods or books, and there is a hanger to put a bag on the back of the chair The results of the redesign of the lecture chair have been able to reduce user complaints by improving the angle of inclination on the back of the chair and the seat mat.